HUBUNGAN PIJAT BAYI TERHADAP KENAIKAN BERAT BADAN BAYI USIA 6- 12 BULAN DI RIU MOM KIDS BABY SPA SUKOHARJO KABUPATEN PATI: The Relationship Of Infant Massage To Weight Gains In 6-12 Months In Riu Mom Kids Baby SPA Sukoharjo, Pati Regency - Diah Ayu Sulastri; Hartotok Hartotok; Siti Muawanah (LPPM - STIKES Pemkab Jombang, 2022)
In optimizing the baby weight in addition to the nutrition provided by the mother, there needs to be a stimulus commonly known as baby massage. The research method type and design used is retrospective. Based on the total sampling technique, the number of samples was 35 respondents. The results showed: 1). Most of the babies at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency, aged 9 months and 12 months old were 7 people (20.0%), 2). All babies were massaged at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency as many as 35 people (100%), 3). Most of the babies at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency, routinely do baby massage as many as 18 people (51.4%), 4). In the discussion, most of the babies at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency were given massage starting at 4 months of age as many as 6 people (17.1%), 5). Most of the babies at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency were given massage 2 x in 1 month as many as 19 people (54.3%), 6).Most of the babies at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency, experienced weight gain as many as 20 people (57.1%) and 7). There is a strong relationship between baby massage and weight gain for babies aged 6-12 months at Riu Mom Kids Baby Spa Sukoharjo, Pati Regency. It is hoped that further researchers are expected to conduct research on infant massage to increase the weight of preschool children and by comparing other stimulus therapies.